Efficacy of Basic Safety Training of BSHM Students in Compass Silang Cavite S.Y. 2022-2023: Guide for Enhance Safety Training: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the efficacy of basic safety training for BSHMstudents in Compass Silang, Cavite, in terms of preventing loss of life, training individuals toreact correctly, aiding treatment, increasing chances of survival, and the challenges theyencountered during the basic safety training. Basic safety training has a huge contribution toour daily lives, and it can be applied anywhere to save the lives of many people. Training isreally important to those people who are pursuing a course that is related to their careerbecause it can enhance their skills and they can gain more knowledge from it.This study shows that the basic safety training in COMPASS Silang, Cavite, has beenachieved in terms of preventing loss of life, training individuals correctly, aiding treatment,increase chances of survival. The things that need to be improved are in the lowest rank,which is basic safety training, which helps spot risky situations and avoid them, learn how tobe calm in emergency situations, completeness and safety of supplies in first aid training aremust, and know the techniques of water survival from the training. The researchers proposedguidelines on how to enhance basic safety training.This study recommends that basic safety training consider the feedback of the trainees, liketheir equipment, which should be hygienic because a lot of people use it, and also that we givethe trainers time to familiarize themselves with the activities so they can apply them correctlyand also consider the health of every person in the training so that assistance is always readyin case of emergency because that’s one of the purposes of basic safety training.
Keywords: Hospitality Management